LENGTH-WEIGHT RELATIONSHIP OF WHIPFIN SILVER-BIDDY, GERRES FILAMENTOSUS CUVIER, 1829 ALONG THE RATNAGIRI, MAHARASHTRA, CENTRAL WEST COAST OF INDIA - SHETKAR, M. B.; NIRMALE, V. H. (Journal of the Inland Fisheries Society of India, 2026)
The length-weight relationship is a valuable tool for understanding the condition, reproductive history, and evolution of aquatic species, as well as for morphological comparisons between organisms and populations (King, 1995). Knowledge of the length-weight relationship between these two variables is essential for growth predictions and total biomass assessments (Gopalakrishnan et al., 2014; Bhakta et al., 2019a, 2019b). It is also used to estimate fish weight from length and to assess stock biomass, which is crucial for fisheries resource management (Froese et al., 2006; Goncalves et al., 1997; Govinda Rao et al., 2014; Bhakta et al., 2022). Length-weight relationships, widely employed to convert length measurements into weight and vice versa, serve as critical parameters in fisheries biology. Such information is essential for deriving equations that convert length into weight to assess stock status (Al Nahdi et al., 2016; Freitas et al., 2017; Jana et al., 2024). This is especially important because length measurements are quicker and more precise under field conditions than weight measurements (Baitha et al., 2018; Borah et al., 2020; Mondal et al., 2023).